2006
DOI: 10.1007/s00192-006-0148-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-perceived outcomes in the treatment of stress urinary incontinence: focus on urethral injection therapy

Abstract: Intervention for stress urinary incontinence (SUI) is generally focused on minimizing urinary leakage. However, the overall impact of SUI therapy on patients' quality of life is, arguably, more important than leakage outcomes. We performed a literature search to investigate the effect of urethral injection therapy on quality of life. Significant quality-of-life improvements have been observed with a number of injectable agents, while there is a distinct lack of correlation between subjective and objective outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A literature review by Chapple et al [10] concluded that QOL improvement after urethral injections appears to be signifi cant and comparable to that obtained with surgery, despite observing superior objective surgical effi cacy.…”
Section: Quality Of Lifementioning
confidence: 93%
“…A literature review by Chapple et al [10] concluded that QOL improvement after urethral injections appears to be signifi cant and comparable to that obtained with surgery, despite observing superior objective surgical effi cacy.…”
Section: Quality Of Lifementioning
confidence: 93%
“…Complication rates were low. A systematic review of patient perceptions of injection therapy identified a randomized trial comparing polydimethylsiloxane with pubovaginal sling; there were no significant differences in satisfaction (60% of injection vs 81% of surgical patients satisfied, P =.41) 58 …”
Section: Resultsmentioning
confidence: 99%
“…Traditionally UBAs have been seen as second line to urethral slings and colposuspension, however, with growing concerns about the use of mesh, and an ageing population, it is important to involve the patient in the decision making. Despite research showing that there is a significantly better objective cure in women who have a colposuspension or a sling procedure compared with urethral bulking, 4 other studies have shown that there is no significant difference in quality of life improvements 35 and therefore more women may opt for the latter due to the minimally invasive approach and reduced morbidity. 7 The search for the ideal bulking agent continues.…”
Section: Discussionmentioning
confidence: 99%